Consumer co‐creation and the impact on intermediaries. Issue 1 (2014) - ,; ,; ,
Abstract : Purpose – While prior studies have examined how loyal customers create value for preferred manufacturers, this study aims to focus on the supply chain and captures the indirect economic and relational benefits and costs of customer value creation on channel intermediaries.Design/methodology/approach – Service‐dominant logic is used to explain the rationale behind consumer contributions and supply chain connectedness in an interactive online world. Drawing from the relevant literature, a conceptual model supported by propositions is presented.Findings – As manufacturers utilize consumer contributions, affiliated intermediaries will report having less informational power, providing less value to the channel, greater benefit‐based and cost‐based dependence, heightened efforts to create channel value, an enhanced reputation and greater sales, and greater collaboration with customers.Research limitations/implications – This conceptual paper is the beginning of an investigation into the pragmatic function of a service‐dominant view as it pertains to a marketing channel. As this avenue for research is further developed, it is important that the propositions included in this study first be examined.Practical implications – Awareness of the underlying logic and the resulting impacts should aid channel intermediaries in realizing their own contributions throughout the manufacturer's value chain and recognizing changes to their positions of power. As a result, channel intermediaries should be better positioned to assess the health and future prospects of the relationship.Originality/value – This work is the first study to examine potential impacts on the intermediary operating in a channel in which the manufacturer is significantly influenced by consumer contributions.